PEMANFAATAN BUAH MANGROVE (Sonneratia caseolaris) MENJADI SABUN CAIR ANTISEPTIK DI DESA ALLANG ASAUDE - Patty, Kristi Lenci; Huwae, Laury Marcia Chara; Mose, Windi; Baszary, Chomsa Dintasari Umi; Nusaly, Windy Natalia (Balobe: Jurnal Pengabdian Masyarakat, 2024)
Alang Asaode Village is one of the villages in West Seram Regency that has a large mangrove forest. Sonneratia caseolaris is one type of mangrove that has a fruit called pedada fruit. Pedada fruit has nutritional content that can be utilized into food products such as jam and syrup because of its high vitamin C content and can also be processed into antiseptic liquid soap. Community service activities in Alang Asaode village in the form of socialization of pedada fruit processing using the fermentation process into economically valuable products such as liquid soap to increase family income.